If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -3)(x + 4) + 8 = x Reorder the terms: (-3 + x)(x + 4) + 8 = x Reorder the terms: (-3 + x)(4 + x) + 8 = x Multiply (-3 + x) * (4 + x) (-3(4 + x) + x(4 + x)) + 8 = x ((4 * -3 + x * -3) + x(4 + x)) + 8 = x ((-12 + -3x) + x(4 + x)) + 8 = x (-12 + -3x + (4 * x + x * x)) + 8 = x (-12 + -3x + (4x + x2)) + 8 = x Combine like terms: -3x + 4x = 1x (-12 + 1x + x2) + 8 = x Reorder the terms: -12 + 8 + 1x + x2 = x Combine like terms: -12 + 8 = -4 -4 + 1x + x2 = x Solving -4 + 1x + x2 = x Solving for variable 'x'. Reorder the terms: -4 + 1x + -1x + x2 = x + -1x Combine like terms: 1x + -1x = 0 -4 + 0 + x2 = x + -1x -4 + x2 = x + -1x Combine like terms: x + -1x = 0 -4 + x2 = 0 Factor a difference between two squares. (2 + x)(-2 + x) = 0Subproblem 1
Set the factor '(2 + x)' equal to zero and attempt to solve: Simplifying 2 + x = 0 Solving 2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + x = 0 + -2 x = 0 + -2 Combine like terms: 0 + -2 = -2 x = -2 Simplifying x = -2Subproblem 2
Set the factor '(-2 + x)' equal to zero and attempt to solve: Simplifying -2 + x = 0 Solving -2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + x = 0 + 2 x = 0 + 2 Combine like terms: 0 + 2 = 2 x = 2 Simplifying x = 2Solution
x = {-2, 2}
| -95.5+x=-32.7 | | X-2=-x+9 | | 90x+36x= | | N^2-10n+14=-2 | | 2(5y-3)= | | 51.2=x+(-31.3) | | 24y+16y= | | 25+40+x=180 | | -5+4+2x=16 | | x+15=-63.4 | | 9x(4x+7b)= | | (y-1)=-12x | | y^2+1=y+5 | | 2xyz+yz= | | 3.2x^2-16.8x-16.8=0 | | 54.2+x=-45.8 | | 9y^2-81y+1=0 | | x+34.2=67.1 | | 6x+7-2x+4=4(3x-5)-17 | | 9=0.4x-8 | | -81=-92.6+x | | M=2(30)+80 | | 2a^2+2=-7 | | M=2x+80 | | 28y+16z= | | -x+58.1=89 | | x+(-67.1)=54.6 | | 65=-16t^2+vt+s | | x^2-4x-12.8=0 | | 4(3x-1)+10= | | 2lnx=ln(6+x) | | -67.5+x=22.7 |